Peru: Determination of the potential collection gap for city taxes, 2014-2021 - Cayatopa Rivera, Luis Enrique (2021)
Objective: Determine the gaps in the potential long-term collection of each tax. Method: The research was approached from a quantitative approach, regarding the analysis of the time series of property and city taxes, from January 2014 to April 2021. In addition, the Hodrick-Prescott filter was used. Results: In the global period of analysis, the difference between the seasonally adjusted collection and the potential collection -trend- was 1 237 million soles, with a contraction -collection gap- total of the taxes analyzed in 2020 of 24.9 million soles. Meanwhile, between 2019 and 2020, the absolute nominal collection of taxes fell by 984.9 million soles, supported by the individual contraction of the following: property tax, city taxes, alcabala tax, vehicle tax, slot machine games tax and the tax on non-sporting public shows of 13.66%; 16.97%; 35.11%; 20.26%; 69.96% and 82.62% respectively. Conclusion: Between 2014 and April 2021 there is a long-term upward trend in the collection of municipal taxes and duties, with downward cyclical contractions such as the one presented in 2020 as consequence of the coronavirus.